Can't use Thales' theorem!

Geometry Level 4

Let a circle with radius 1 have centre O O , and let A B AB be its diameter . C C , D D and E E are collinear points in that order such that C C is on A B AB extended closer to A A , D D and E E are on the circle and B E = E D = D C BE=ED=DC . If the value of cos E O B \cos \angle EOB can be represented as a b \dfrac {a}{b} , where a a is an integer , b b is a positive integer and both are coprime, find the value of a + b a+b .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Wen Z
Aug 30, 2016

E O EO is an anble bisector (of D E B \angle DEB ) so C E E B = C O O B \frac{CE}{EB}=\frac{CO}{OB} . Because A O = O B AO=OB , C A = A O = O B = O E = r CA=AO=OB=OE=r where r r is the radius of the circle. Let B E = E D = D C = x BE=ED=DC=x Now by power of a point , we have

C D C E = C A C B CD\cdot CE=CA\cdot CB

which is the same as

2 x 2 = 3 r 2 2x^2=3r^2

Now by the cosine rule on E O C \bigtriangleup EOC we have

E B 2 = O E 2 + O B 2 2 O E O B cos E O B EB^2=OE^2+OB^2-2OE\cdot OB \cos \angle EOB

i.e

x 2 = 2 r 2 = 2 r 2 cos E O B x^2=2r^2=2r^2 \cos \angle EOB

Multiplying by two yields

2 x 2 = 4 r 2 ( 1 cos E O B ) 2x^2=4r^2(1-\cos \angle EOB)

Lastly equating this with the power of a point equation we have

3 r 2 = 4 r 2 ( 1 cos E O B ) 3r^2=4r^2(1-\cos \angle EOB)

which yields

1 cos E O B = 3 4 1-\cos \angle EOB=\frac{3}{4} ,

which yields

cos E O B = 1 4 \cos \angle EOB=\frac{1}{4}

Therefore a + b = 5 a+b=\fbox{5}

Just a remark, since you're given that the circle is a unit circle you could say r = 1 r=1 . But that doesn't really affect the proof

Wen Z - 4 years, 9 months ago

Log in to reply

Yep. You nailed the proof. Instead of using angle bisector theorem, you could instead show C E B = C O E \angle CEB = \angle COE , so Δ C O E Δ C E B \Delta COE \sim \Delta CEB , and determine the value of C A CA as a result to use in the power of a point.

Sharky Kesa - 4 years, 9 months ago

Log in to reply

I had that in my diagram but for the proof I realised that I could cut out a lot of redundant stuffs.

Wen Z - 4 years, 9 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...